2014
DOI: 10.1002/2014jd022265
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of entrainment‐mixing mechanisms in cumulus clouds

Abstract: This work empirically examines the dependence of entrainment-mixing mechanisms on the averaging scale in cumulus clouds using in situ aircraft observations during the Routine Atmospheric Radiation Measurement Aerial Facility Clouds with Low Optical Water Depths Optical Radiative Observations (RACORO) field campaign. A new measure of homogeneous mixing degree is defined that can encompass all types of mixing mechanisms. Analysis of the dependence of the homogenous mixing degree on the averaging scale shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 54 publications
2
72
1
Order By: Relevance
“…Within these ranges the effective radius can change by more than 10-15 %. Standard mixing diagrams do not include this range that, to our knowledge, has never been investigated despite the fact that multiple in situ measurements indicate its existence (e.g., Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Within these ranges the effective radius can change by more than 10-15 %. Standard mixing diagrams do not include this range that, to our knowledge, has never been investigated despite the fact that multiple in situ measurements indicate its existence (e.g., Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The criterion of the in‐cloud drizzle water content (radius > 25 μm) averaged over the observation period of the flight smaller than 0.005 g m −3 is used to select the nondrizzling cumulus clouds. In total, there are 186 nondrizzling growing cumulus clouds from eight flights (22–24 May, 11 June, 19 June, 23 June, 24 June, and 26 June 2009); the same data set was used in Cheng et al () and Lu et al (). As shown in Table , the total number of cloud droplet size distributions was 13,652 from 186 clouds.…”
Section: Observational Analysismentioning
confidence: 99%
“…The existence of the turbulent energy cascade implies that there is a range of turbulence time scales, from the large‐scale eddy turnover time (short: large‐eddy time) T L to the dissipation (or Kolmogorov) time τ η . It is thus possible that within the turbulence cascade, both D a > 1 and D a < 1 can exist at different spatial scales, so that one can also expect a different microphysical response at different scales (Andrejczuk et al, ; Beals et al, ; Korolev & Mazin, ; Lehmann et al, ; Lu et al, , ; Siebert et al, ). For example, some DNS results suggested that a transition from inhomogeneous to homogeneous mixing could lead to an inhomogeneous offset in the microphysical trajectory in a mixing diagram (Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%